The day after mowing: Time and type of mowing influence grassland arthropods - Konstans Wells (Ecological Applications, 2024)
Recent losses in the abundance and diversity of arthropods have been documented in many regions and ecosystems. In grasslands, such insect declines are largely attributed to land use, including modern machinery and mowing regimes. However, the effects of different mowing techniques on arthropods remain poorly understood. Using 11 years of data from 111 agricultural grassland plots across Germany, we analyzed the influence of various grassland management variables on the abundance and abundance-accounted species richness of four arthropod orders: Araneae, Coleoptera, Hemiptera, and Orthoptera. The analysis focused on detailed mowing information, for example, days after mowing and mower type, and compared their effect with other aspects of grassland management, that is, rolling, leveling, fertilization, and grazing. We found strong negative effects of mowing on all four arthropod orders, with arthropod abundance being lowest directly after mowing and steadily increasing to three to seven times the abundance after 100 days post-mowing. Likewise, Hemiptera and Coleoptera species richness was 30% higher 100 days after mowing. Mower width showed a positive effect on Orthoptera abundance, but not on the other arthropods. Arthropod abundance and Coleoptera species richness were lowest when a mulcher was used compared to rotary or bar mowers. In addition to mowing, intensive grazing negatively affected Orthoptera abundance but not the other orders. Mowing represents a highly disturbing and iterative stressor with negative effects on arthropod abundance and diversity, likely contributed by mowing-induced mortality and habitat alteration. While modifications of mowing techniques such as mower type or mowing height and width may help to reduce the negative impact of mowing on arthropods, our results show that mowing itself has the most substantial negative effect. Based on our results, we suggest that reduced mowing frequency, omission of mowing in parts of the grassland (refuges), or extensive grazing instead of mowing have the greatest potential to promote arthropod populations.